1996
DOI: 10.1109/81.536749
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the design of digital integrators

Abstract: 785coefficients -ym (location of the borders between the regions). Thus, the behavior of an n-dimensional system having a piecewise-linear continuous vector field with o-regions and parallel boundaries (4) is uniquely determined by the n eigenvalues of A, n eigenvalues of A + deT, n . a eigenvalues of A + bmey for m = 1, . . . , a, and a locations of the borders between the regions which makes a total of 2 . n + n . a + a parameters. IV. CONCLUSIONWe have shown that vector fields in Lur'e form having identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 5 publications
0
47
0
Order By: Relevance
“…Further, the percentage relative errors (PREs) of the obtained recursive digital differentiators from the ideal differentiators of corresponding time-constants are shown in Figure 2. From Figures 1 and 2, it is observed that the few optimized designs for non unity time-constants may be wideband with lower percentage relative error compared to the unity timeconstant design as in (11). As an example, the proposed design of proportion constant (13) can also be converted to design a recursive digital differentiator of unity time-constant.…”
Section: Design Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the percentage relative errors (PREs) of the obtained recursive digital differentiators from the ideal differentiators of corresponding time-constants are shown in Figure 2. From Figures 1 and 2, it is observed that the few optimized designs for non unity time-constants may be wideband with lower percentage relative error compared to the unity timeconstant design as in (11). As an example, the proposed design of proportion constant (13) can also be converted to design a recursive digital differentiator of unity time-constant.…”
Section: Design Methodologymentioning
confidence: 99%
“…The corresponding digital differentiator of unity time-constant is given in (16). The recursive wideband digital integrators can be easily obtained by inverting the transfer functions of proposed recursive digital differentiators as in (11)(12)(13)(14)(15)(16). Table 2 shows the values of proportion constants i K with the corresponding timeconstants for different designs of recursive digital integrators.…”
Section: Design Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The objective is to design these differintegrators so that they meet the given requirements with sufficient accuracy. Various approximations of ideal differintegrators have been reported in the literature [1][2][3][4][5][6][7][8][9]. Al-Alaoui [1] has proposed the interpolation method to design a digital integrator.…”
Section: Introductionmentioning
confidence: 99%
“…Schneider et al [2] have also proposed a digital integrator by modifying the Newton-Cotes integration rule. Papamarkos and Chamzas [3] used the linear programming optimization method in designing digital integrators. Ngo [4] used the closed form of the Newton-Cotes integration rule to design a digital integrator.…”
Section: Introductionmentioning
confidence: 99%